Hypercalcemia in the Presence of an Ectopic Mediastinal Mass - Robert K. Strother; Matthew Meunier MD (SAGE Publishing, 2020)
A 72-year-old gentleman who presented to the outpatient clinic for a preventive health appointment with symptoms of depression and fatigue was found to have persistent hypercalcemia on routine laboratory monitoring. Initial laboratory testing was consistent with primary hyperparathyroidism with elevation in parathyroid hormone and low vitamin D levels. Further imaging demonstrated an ectopic mediastinal parathyroid adenoma. The ectopic lesion was treated surgically and lead to normalization of calcium levels and objective improvement in depressive symptoms. Primary hyperparathyroidism, which can be secondary to an adenoma, multigland hyperplasia, or neoplasm, can lead to the development of bone pain, fractures, and nephrolithiasis among other symptoms. The evaluation of hypercalcemia and the identification of primary hyperparathyroidism are important for the primary care physician to recognize so as to reduce disease morbidity as well as identify patients in need of further specialty care.